2018
DOI: 10.3389/fpsyt.2018.00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoresistant Severe Mental Health Disorders in Children and Adolescents: Functional Abnormalities of Cytochrome P450 2D6

Abstract: BackgroundSevere mental health disorders in children and adolescents represent a major public health problem. Despite adequate drug treatment, some patients develop pharmacoresistant disease. As a consequence, physicians are confronted with prescribing challenges, prolonged hospitalization and increased risk of adverse events, thus aggravating short-, medium-, and long-term prognosis. The majority of psychotropic treatments, particularly antipsychotics and antidepressants, are metabolized at hepatic level by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…Environmental chemicals and toxicants: In the last few years, epidemiologic investigations indicated that prenatal exposure to chemical and toxic factors such as air pollution, pesticides, materials used in the plastic industry and heavy metals may increase the risk of ASD [39,40,62,63,64]. Possible mechanisms behind the association between these environmental risk factors and ASD are not only their interactions with genetic factors, and/or epigenetic marks leading to a diminished ability to detoxify xenobiotics [65,66] but also their potential role in triggering neuro-inflammation and oxidative stress that lead to neurobiological and neurotransmitter alterations and abnormalities in signaling pathways [63].…”
Section: Prenatal Periodmentioning
confidence: 99%
“…Environmental chemicals and toxicants: In the last few years, epidemiologic investigations indicated that prenatal exposure to chemical and toxic factors such as air pollution, pesticides, materials used in the plastic industry and heavy metals may increase the risk of ASD [39,40,62,63,64]. Possible mechanisms behind the association between these environmental risk factors and ASD are not only their interactions with genetic factors, and/or epigenetic marks leading to a diminished ability to detoxify xenobiotics [65,66] but also their potential role in triggering neuro-inflammation and oxidative stress that lead to neurobiological and neurotransmitter alterations and abnormalities in signaling pathways [63].…”
Section: Prenatal Periodmentioning
confidence: 99%
“…Administration of FLX by intranasal route is therefore expected to decrease the DDI at intestinal and hepatic tissues as well as to evade the BBB and the P-glycoprotein therein expressed and that has been suggested to be involved in pharmacoresistant depression. Moreover, the intranasal route also decreases drug systemic exposure, and consequently adverse effects [17]. As such, FLX is herein hypothesized as a SSRI model drug to be encapsulated within lipid nanoparticles for intranasal delivery.…”
mentioning
confidence: 99%
“…GWAS analysis supports CACNA1C’s participation in bipolar disorder, a behavioral disorder related to abnormal depression and elevated moods 43 . Anxiety and substance related disorders are commonly associated with bipolar disorders 44 . This suggests some health conditions are connected.…”
Section: Resultsmentioning
confidence: 99%